Vitamin D Supplementation for the Treatment of Depressive Symptoms in Women with Type 2 Diabetes: A Randomized Clinical Trial. (3rd March 2022) - Penckofer, Sue; Ridosh, Monique; Adams, William; Grzesiak, Meghan; Woo, Jennifer; Byrn, Mary; Kouba, Joanne; Sheean, Patricia; Kordish, Colleen; Durazo-Arvizu, Ramon; Wallis, Diane; Emanuele, Mary Ann; et al.
Abstract : Aim . To determine the efficacy and safety of vitamin D3 supplementation in reducing depressive symptoms in women with type 2 diabetes (T2D), depression, and low vitamin D. Methods . In this double-blind randomized active comparator-controlled trial, women with significant depressive symptoms as assessed by the Center for Epidemiologic Studies Depression (CES-D) scale received weekly oral vitamin D3 supplementation (50, 000 IU) or an active comparator (5, 000 IU) for 6 months. Assessments of vitamin D, 25-hydroxyvitamin D [25 (OH) D], and depression were measured at baseline, 3 months, and 6 months. Results . A total of 129 women were randomized, from which 119 completed the study (57 in lower dose and 62 in higher dose). Participants had an average 25 (OH) D and HbA1c of 20.8 ng/mL and 7.8%, respectively, at baseline. They were diverse (48% Black) and had a mean age of 50 and T2D for about 8 years. Upon completion of vitamin D3 supplementation, serum 25 (OH) D levels increased with 50, 000 IU (+34 ng/mL) and 5, 000 IU (+10 ng/mL). There was no difference in CES-D scores by treatment dose. Overall, depressive symptoms significantly improved over time with an average CES-D decline of 12.98 points (95% CI: −15.04 to −10.93; p < 0.001 ). Among women with moderate baseline depressive symptoms, those receiving the lower dose had nominally lower depression scores at follow-up than those in the higher dose cohort. Among women with severe baseline depressive symptoms, the improvement in follow-up depression scores was the same regardless of dose. Conclusions . There was no difference in the dosing effect of vitamin D3 supplementation for the treatment of depressive symptoms in women with T2D who present with significant symptoms and low vitamin D. Regardless of the dose, participants' mood improved over time. Further study of vitamin D to target depressive symptoms in comorbid populations is needed.